Performance of Closed-Ended Mutual Funds: A Test of Market Efficiency - Karki, Dipendra; Upreti, Suresh Kumar (Nepal Journal of Multidisciplinary Research, 2024)
Background: Mutual funds, known for aggregating funds from a diverse investor base, play a crucial role in managing small funds smartly. This study evaluates the performance of selected closed-ended mutual funds and examines market efficiency in Nepal. Methods: Using a descriptive and casual-comparative research design, the study spans forty-eight months from January 15, 2018, to January 14, 2022. Monthly data from five mutual funds are analyzed, with metrics such as the Treynor ratio, Sharpe ratio, and Jensen alpha. The study variables include market returns, assets, expense ratios, fund age, liquidity, and mutual fund returns. Various statistical tests, including correlation analysis, Integrated Ranking Analysis, ANOVA test, t-test, and P-value tests, are conducted to determine the significance and statistical relevance of the study variables. Results: The findings reveal that mutual fund performance is influenced by factors such as return, age, liquidity, asset, and expense ratio. Expense ratio and age emerge as the most impactful factors, demonstrating a statistically significant relationship with market return (p < 0.05). All selected mutual funds outperform the market return (NEPSE), with Sanima Equity Fund securing the top rank in all three measures. Conclusion: The Sharpe ratio, Treynor ratio, and Jensen alpha measures for mutual funds surpass those of the market, indicating market inefficiency in its semi-strong form. Novelty: This study uniquely evaluates closed-ended mutual funds using comprehensive performance metrics, demonstrating their significant outperformance compared to market benchmarks. It underscores their effectiveness in actively managing passive funds and challenges the efficient market hypothesis.